Allozyme differentiation of two populations of the genus Neoplecostomus Eigenmann & Eigenmann, 1888 (Teleostei, Loricariidae) from the upper Paraná River basin, Brazil - Reusing, Ana Flávia; Renesto, Erasmo; Roxo, Fábio F. [UNESP]; Zawadzki, Cláudio H. [UNESP] (Sociedade Brasileira de Genética, 2011)
Allozyme electrophoresis was used to examine 12 enzymatic systems in two populations of the genus Neoplecostomus from the Paraná River basin. Samples of Neoplecostomus sp. 1 were collected in Paraitinguinha stream of the Tietê River basin, in the municipality of Salesópolis, São Paulo State, and those of Neoplecostomus sp. 2 from São Domingos stream of the Rio Grande River basin, in the municipality of Muzambinho, Minas Gerais State. The genetic variability of the two populations was estimated by Nei's expected heterozygosity and was considered lower than average for populations of freshwater fish. The proportion of polymorphic loci was low (only 5.26% for the locus Idh). The low frequency of heterozygosity for both populations revealed a high fixation of alleles for each locus. Homozygote excess was observed in both populations. The values of Nei's genetic identity and the presence of loci with different allele frequencies in both populations may imply that the two populations belong to different species. The genetic variability between populations was compared to other data for loricariids.
Keywords: allozymes; genetic variability; Neoplecostominae; Neotropical fishes